A dielectric barrier discharge terminally inactivates RNase A by oxidizing sulfur-containing amino acids and breaking structural disulfide bonds. (16th November 2015) - Lackmann, J-W; Baldus, S; Steinborn, E; Edengeiser, E; Kogelheide, F; Langklotz, S; Schneider, S; Leichert, L I O; Benedikt, J; Awakowicz, P; Bandow, J E
Abstract: RNases are among the most stable proteins in nature. They even refold spontaneously after heat inactivation, regaining full activity. Due to their stability and universal presence, they often pose a problem when experimenting with RNA. We investigated the capabilities of nonthermal atmospheric-pressure plasmas to inactivate RNase A and studied the inactivation mechanism on a molecular level. While prolonged heating above 90 °C is required for heat inactivating RNase A, direct plasma treatment with a dielectric barrier discharge (DBD) source caused permanent inactivation within minutes. Circular dichroism spectroscopy showed that DBD-treated RNase A unfolds rapidly. Raman spectroscopy indicated methionine modifications and formation of sulfonic acid. A mass spectrometry-based analysis of the protein modifications that occur during plasma treatment over time revealed that methionine sulfoxide formation coincides with protein inactivation. Chemical reduction of methionine sulfoxides partially restored RNase A activity confirming that sulfoxidation is causal and sufficient for RNase A inactivation. Continued plasma exposure led to over-oxidation of structural disulfide bonds. Using antibodies, disulfide bond over-oxidation was shown to be a general protein inactivation mechanism of the DBD. The antibody's heavy and light chains linked by disulfide bonds dissociated after plasma exposure. Based on their ability to inactivate proteins by oxidation of sulfur-containing amino acids and over-oxidation of disulfide bonds, DBD devices present a viable option for inactivating undesired or hazardous proteins on heat or solvent-sensitive surfaces.